Improving Student Learning Outcomes Through The Use of Kahoot Media - Karliana Indrawari; Idi Warsah; Aini Syahira Jamaluddin (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Abstract. The purpose of this research is to determine the application of kahoot media in the Islamic Education Methodology course at the Islamic Education Study Program, IAIN Curup; to determine student learning outcomes in the Islamic Education Methodology course after applying kahoot media in the Curup Islamic Education Study Program; and to determine the effectiveness of the application of kahoot media on student learning outcomes in the Islamic Education Methodology course at the Islamic Education Study Program.The research method is qualitative, and the research subject is a lecturer at IAIN Curup's Islamic Education Institute. Observation, interviews, and documentation are all methods for gathering data. Techniques for data reduction, data analysis, and data conclusionsLecturers must be creative and innovative in their use of media. The use of kahoot media in the classroom revealed numerous benefits and drawbacks. When Kahoot media is used effectively in class, learning objectives can be met. The meaning of the material presented is explained by media kahoot. Learning with this kahoot media makes learning more enjoyable and prevents students from becoming bored while taking difficult-to-understand lessons.